Higher Serum Levels of Lactate Dehydrogenase Before Microsurgery Predict Poor Outcome of Aneurysmal Subarachnoid Hemorrhage - Zheng, Shufa; Wang, Haojie; Chen, Guorong; Shangguan, Huangcheng; Yu, Lianghong; Lin, Zhangya; Lin, Yuanxiang; Yao, Peisen; Kang, Dezhi (Frontiers in Neurology, 2021)
Introduction: We explored the clinical significance of serum lactate dehydrogenase(LDH) level in aSAH patients treated by microsurgical clipping in our institution, to test the hypothesis that higher preoperative serum level of LDH predicts the outcome of aSAH patients at 3 months. Methods: The aSAH patients in our institution between 2010 and 2018 were collected. Age, sex, history of smoking, drinking, medical history, Hunt-Hess and Fisher grade, aneurysm location, delayed cerebral ischemia (DCI), intracranial infection, hydrocephalus, pneumonia and preoperative serum LDH level within 24 hours after aSAH were recorded. To define the relation between serum LDH level and clinical outcome of aSAH patients, we investigated whether preoperative serum LDH level was associated with Hunt-Hess grade, Fisher grade and neurological functional outcome. Results: A total of 2054 aSAH patients were collected, and 874 patients treated by microsurgical clipping were enrolled. The average serum LDH level(U/L) in the good outcome group (180.096±50.237) was obviously lower than that in the poor outcome group (227.554±83.002)(p<0.001). After propensity-score matching, average serum LDH level(U/L) in the good outcome group (205.356±76.785) was still lower than that in the poor outcome group (227.119±86.469)(p=0.029). The area under the receiver operating characteristic (ROC) curve was 0.702(95% confidence interval [CI], 0.650 - 0.754; p<0.001). The optimal cutoff value for serum LDH level as a predictor for 3-month poor outcome (mRS>2) was determined as 201.5U/L in the ROC curve. The results revealed that Hunt-Hess grade，Fisher grade, DCI, pneumonia, serum LDH(>201.5U/L) were significantly associated with poor outcome. After propensity-score matching analysis, serum LDH(>201.5U/L) level was still considered as an independent risk factor of poor outcome (OR 2.426, 95% CI 1.378-4.271, p = 0.002). Serum LDH level was associated with Hunt-Hess and Fisher grade. It was also shown that serum LDH level correlated with neurological functional outcome (p<0.001). Conclusions: Our finding showed that higher preoperative serum level of LDH correlated with Hunt & Hess grade, Fisher grade and neurological functional outcome, and predicted the outcome of aSAH treated by microsurgical clipping at 3 months, which was involved in the related mechanisms of early brain injury and showed its potiential clinical significance in aSAH patients.